MiRNA-214 promotes the pyroptosis and inhibits the proliferation of cervical cancer cells via regulating the expression of NLRP3 - Yu, Shunrui; Zhao, Na; He, Mengya; Zhang, Kai; Bi, Xuehui (Cellular and Molecular Biology, 2020)
Inflammasome mediates the maturation of interleukin-1Î² (IL-1Î²) and IL-18, triggers the pyroptosis and associates with multiple autoimmune diseases. In light of this, we hope to investigate the regulatory role of miRNA-214 in the inflammasome of cervical cancer. With the samples collected from 50 cervical cancer patients and 50 age-matched healthy subjects, real-time PCR and Western blotting were employed to detect the mRNA and/or protein expression profiles of the NOD-like receptor protein family, including NLRP1, NLRP3, NLRC4, Caspase-1, IL-1Î², IL-18 and miR-214. Corresponding plasmids were used to transfect the Hela, HCC94, Siha or HUCEL normal cell lines to upregulate or downregulate the expression of targeted genes and to construct the cervical cancer models on rats. In addition, RT-PCR and Western blot were also considered to detect the expression of miR-214 and pyroptosis-related genes, while the pyroptosis of cells was evaluated by using the caspase-1 activity detection kit. Downregulation of miR-214 was found in the cervical cancer patients and the cervical cancer cell lines (** P <0.01), while overexpression of miR-214 could induce the pyroptosis of cervical cancer cell by targeting NLRP3. In cervical cancer patients, miR-214 and NLRP3 are downregulated, while upregulation of miR-214, by enhancing the expression of NLRP3, can advance the pyroptosis of cervical cancer cells. In addition, we, for the first time, clarify the correlation of cervical cancer with the miR-214 and NLRP3.